Os Marajós em relatos: narrativas museais de viajantes no século XIX - ARAÚJO, Lucas Monteiro de (2019)
This work analyzes representations of marajoara culture in narratives of travelers in the nineteenth century. The marajoara’s Amazon was intensely written by naturalists, anthropologists, zoologists, botanists, among others, because it is a region with a rich natural and cultural heritage. We seek to do a parallelism between the conceptual notion of the museum and the texts, understanding that, similarly that institution such literature also have the ability to express themselves as museum experience. Going beyond reporting the adventures of their authors, the narratives relate habits, describe places, report myths, legends, local knowledge and practices. In further studies, we can still perceive conflicts of perceptions, membership ties and cosmologies of marajoaras populations, materialized in books, journals, newsletters and magazines. Thus, we conclude that, from the researches made, that the texts can be understood as a great conceptual Museum.